Measure Counter-Suggestion at University Students (Raparin Journal of Humanities (RJH), 2022)
This research aims to measure counter-suggestion students at University and identify its levels according to variable (gender ) ,The study sample consisted of )302( students at Salahaddin University-Erbil who were selected in a random manner in Society different colleges at Salahaddin University namber of (21105) students for the academic year )2020-2021( at morning study , the researchers construction the scale counter-suggestion as composite (62( items, after derivatio the honesty and stability of the construction as well as measuring instrnment, the researchers applied the scale counter-suggestion as composite(62( items at sampling final form of the research, for statistical means of data analysis of usage (Spss) program, showed the following search results: 1- The members of the study sample in general have a good level of counter-suggestion.• There are statistical differences between students according to the gender variable and it is more in favor of the male sample.In the light of the results of the study, a number of conclusions and recommendations were reached and the researchers made a number of recommendations and proposals at the end of the study.